PLGA Nanoparticles for Peptide Receptor Radionuclide Therapy of Neuroendocrine Tumors: A Novel Approach towards Reduction of Renal Radiation Dose - Arora, Geetanjali; Shukla, Jaya; Ghosh, Sourabh; Maulik, Subir Kumar; Malhotra, Arun; Bandopadhyaya, Gurupad (PloS one, 2012)
Peptide receptor radionuclide therapy (PRRT), employed for treatment of neuroendocrine tumors (NETs) is based on over-expression of Somatostatin Receptors (SSTRs) on NETs. It is, however, limited by high uptake and retention of radiolabeled peptide in kidneys resulting in unnecessary radiation exposure thus causing nephrotoxicity. Employing a nanocarrier to deliver PRRT drugs specifically to the tumor can reduce the associated nephrotoxicity. Based on this, (177)Lu-DOTATATE loaded PLGA nanoparticles (NPs) were formulated in the present study, as a potential therapeutic model for NETs. DOTATATE was labeled with Lutetium-177 ((177)Lu) (labeling efficiency 98%; R(f)∼0.8). Polyethylene Glycol (PEG) coated (177)Lu-DOTATATE-PLGA NPs (50:50 and 75:25) formulated, were spherical with mean size of 304.5±80.8 and 733.4±101.3 nm (uncoated) and 303.8±67.2 and 494.3±71.8 nm (coated) for PLGA(50:50) and PLGA(75:25) respectively. Encapsulation efficiency (EE) and In-vitro release kinetics for uncoated and coated NPs of PLGA (50:50 & 75:25) were assessed and compared. Mean EE was 77.375±4.98% & 67.885±5.12% (uncoated) and 65.385±5.67% & 58.495±5.35% (coated). NPs showed initial burst release between 16.64-21.65% with total 42.83-44.79% over 21 days. The release increased with coating to 20.4-23.95% initially and 60.97-69.12% over 21 days. In-vivo studies were done in rats injected with (177)Lu-DOTATATE and (177)Lu-DOTATATE-NP (uncoated and PEG-coated) by imaging and organ counting after sacrificing rats at different time points over 24 hr post-injection. With (177)Lu-DOTATATE, renal uptake of 37.89±10.2%ID/g was observed, which reduced to 4.6±1.97% and 5.27±1.66%ID/g with uncoated and coated (177)Lu-DOTATATE-NP. The high liver uptake with uncoated (177)Lu-DOTATATE-NP (13.68±3.08% ID/g), reduced to 7.20±2.04%ID/g (p = 0.02) with PEG coating. PLGA NPs were easily formulated and modified for desired release properties. PLGA 50:50 NPs were a more suitable delivery vehicle for (177)Lu-DOTATATE than PLGA 75:25 because of higher EE and slower release rate. Reduced renal retention of (177)Lu-DOTATATE and reduced opsonisation strongly advocate the potential of (177)Lu-DOTATATE-PLGA-PEG NPs to reduce radiation dose in PRRT.